DEVELOPMENT OF OPHIOLITIC PERSPECTIVES ON MODELS OF OCEANIC MAGMA CHAMBERS BENEATH ACTIVE SPREADING CENTERS - Thy P.; Dilek Y. (My University, 2003)
Ophiolites played a minor role in the formulation of the ideas of the history and evolution of the ocean floor because initially they were not interpreted as oceanic in origin. Early researchers working on ophiolites were late in claiming their oceanic origin. Ophiolites were universally considered to be large sill intrusions or thick lava flows emplaced from an abyssal substratum into subsiding, marginal sedimentary basins. Such large pools of basaltic magma were proposed to have differentiated internally as a result of crystallization within an outer veneer of a giant lava pillow. It was first with the emergence of the theory of plate tectonics that it became possible to distinguish between mantle rocks and crustal intrusive plutons. This development led to the recognition of fossil magma chambers in ophiolites. Plate tectonic models implied that basaltic magma either erupted directly on the seafloor or accumulated in crustal chambers beneath spreading centers. The first models developed in the late 1960s for the structure of modern oceanic crust did not include lower crustal magma chambers; however, subsequent models formulated in the early 1970s incorporated the existence of magma chambers, but with little reference to ophiolite studies. Oceanic magma chambers were seen as large, continuously growing entities keeping pace with seafloor spreading and steady-state magma supply. This magma chamber interpretation was very influential and contained the key elements soon adapted by many of the subsequent studies of ophiolites. Such ophiolitic magma chamber models were extended to the oceans in the 1980s, inferring the size, shape, and evolution of magma chambers beneath active spreading centers. The challenge to the steady-state magma chamber model came from geophysical and theoretical modeling of modern oceanic crust. These studies revealed that large magma chambers could not exist beneath slow-spreading centers, and that they might be present beneath fast-spreading centers only as a thin magma lens on top of a large crystal mush. Other predictions suggested the presence of small magma chambers in broad zones under the axial valley and emphasized the intermittent nature of crustal chambers as a result of the interplay between tectonic and magmatic processes. This modeling of oceanic crust made little use of observations from ophiolites. The general image that emerged in the 1990s was that magma chambers beneath fast-spreading centers were largely filled with crystal mush containing only small percentages of melt. The large molten chambers envisioned during the proceeding three decades have thus vanished and been replaced by crystal mush chambers. The most important implication of this interpretation for the origin of ophiolites is that layering commonly observed in gabbros is likely to have formed as a result of crustal strain, not from direct deposition or crystallization on chamber walls. Deep drilling during the last ten years into in situ modern oceanic crust near active spreading centers has supported the existence of crystal mush zones. A surprising discovery has been the preservation of evolved gabbros within primitive host gabbro sequences. The evolved gabbros were interpreted to represent the interstitial melt that migrated upward and laterally as a result of compaction and/or tectonic deformation. The interaction between new magma seeping up from beneath the chamber and the lower strata of the mush makes the mush zone grow. Detailed field studies of ophiolites in recent years have demonstrated that new magma may form sill complexes in crystal mushes. The mush and sill complexes act as a reactive filter, modifying the migrating residual melt and controlling the composition of the residual melt, which eventually reaches the magma lens or gets erupted as lavas on the seafloor. Our understanding of oceanic magma chambers has been much influenced by direct observations and careful fieldwork in plutonic complexes of ophiolites. The revival of systematic field and petrographic studies in ophiolites is a necessary approach to further advance our understanding of oceanic magma chambers and the magmatic and tectonic processes associated with the evolution of oceanic crust.